The occult world - Partridge, Christopher (The Routledge worlds, 2015)
"This volume presents students and scholars with a comprehensive overview of the fascinating world of the occult. It explores the history of Western occultism, from ancient and medieval sources via the Renaissance, right up to the nineteenth and twentieth centuries and contemporary occultism. Written by a distinguished team of contributors, the essays consider key figures, beliefs and practices as well as popular culture"--